SUSTAINABILITY STATUS ANALYSIS OF ESTUARIAN MANAGEMENT (CASE STUDY: KUALA TRIPA ESTUARIAN WATERS) NAGAN RAYA REGENCY - Edwarsyah Edwarsyah; Nabil Zurba; Putri Faza Syahida; Muhammad Banda Selamat (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2021)
The damage in Kuala Tripa Estuary needs sustainable management. This study is aim to determine the sustainability status of the ecological, social, economic, technological and institutional dimension as well as alternative directions for development policies in sustainable management of the Kuala Tripa estuary. This study uses a descriptive approach with the maintenance of survey methods and case studies. The study was conducted from May to July 2021. A total of 11 respondents were selected using purposive sampling and proportional sampling methods. Water quality measurements were also conducted (Salinity, dissolved oxygen, pH, temperature, BOD and COD) at three station points. To test the water quality, BOD (Bisolved Oxygent Demand) and COD (Chemical Oxygent Demand) were analyzed at the Aceh Health Laboratory. The data were analyzed using RAPFISH (Rapid Apprasial for Fisheries) software. The measured attributes are the ecological, social, economic, technological and institutional dimensions. The status of the Multi-Dimensional Scaling estuarine sustainability index status of Kuala Tripa is quite sustainable with a score of 55.41. The most sensitive attributes from the leverage analysis are used to identify efforts (policy recommendations) through the AHP (Analytical Hierarchy Process) method. The first alternative is water extension policy with a priority value of 0.29.